Comprehensive analysis of circRNAs expression profiles in different periods of MDBK cells infected with bovine viral diarrhea virus. (August 2019) - Li, Cunyuan; Li, Xiaoyue; Hou, Xiaoxu; Ni, Wei; Zhang, Mengdan; Li, Huixiang; Xu, Yueren; Hazi, Wureli; Ma, Qiman; Zhang, Yunfeng; Wang, Dawei; Hu, Shengwei
Abstract: CircRNAs play an important regulatory role in the regulation of disease. However, we have a limited understanding of the role of circRNAs in the host's complex protective and pathological mechanisms of BVDV infection. Transcriptome analysis of circRNAs in host cells after BVDV infection may allow us to understand the biological functions of circRNAs in the regulation of BVDV infection. Here, we identified a total of 19, 118 circRNAs from the MBDK cells (at 12 h, 24 h, and 48 h post-infection) infected with BVDV by using RNA-seq technology. We confirmed several circRNAs using RT-PCR and DNA sequencing, and qRT-PCR analysis was performed to identify several circRNAs expression and circRNAs resistance to RNase R digestion. GO (Gene Ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes) enrichment analysis showed that the host genes of differentially expressed circRNAs were involved in the regulation of cell proliferation, apoptosis, cycle and viral infection related signaling pathways. These results indicate that circRNA in host cells plays a broad regulatory role after BVDV infection and provides a valuable resource for studying circRNA biology in host cells after BVDV infection. Highlights: The expression profile of circRNAs in MDBK cells infected with BVDV was described. Analysis of differentially expressed circRNAs in different periods of MDBK cells infected with BVDV. GO and KEGG analysis showed that the hosting genes of circRNAs were associated with regulation of BVDV infection process.